Design and fabrication of automated plant watering system via arduino-based sensor powered by photovoltaic (PV) panel power supply - Muhammad Amirul Afiq bin Samsudin (2023)
The automatic plant watering system via Arduino-based sensor powered by photovoltaic (PV) panels power supply is introduced in which it is considered as one of the most beneficial autonomous systems that assists people in their daily activities by reducing or completely replacing their effort. This system user sensor technology along with Arduino microcontroller and other electronics to behave like a switch which senses soil moisture level and detects rainfall and in the same time irrigates the plant when necessary.